Ahmed bin Majid acquitted of the charge of guiding the Portuguese to India (Journal of the College of Basic Education, 2023)
I chose the subject of the study of the navigator Ahmed bin Majid, the skipper, writer, poet and astronomer.And the geographer, after I found a document proving the innocence of Ibn Majid of his guidance to the Portuguese in the year2000 AD, despite his valuable achievement and his marine sciences and writings that he left to the world, withoutAl-Nahrawali eighty years after this event, the trip and accused him of the arrival of Portugal toIndia, without relying on an argument or evidence to prove the accusation against him, while contemporary historiansFor the event, they did not mention Ahmed bin Majid, nor Vasco de Gama, nor anything about the trip, which led toto Arab prejudice against him, after the wide fame he gained, and what distinguishes Ibn MajidThe Arab navigators did not have a state that would support them and enable them to expand their activities, but they were lions.sea and work without official protection from the state and all their scientific achievementsAnd the expansion of their field of activity was thanks to their knowledge, efforts and valor.In the subject of the research, I dealt with two topics: the first topic included the life of Ibn Majid, thenI touched on his marine works and his writings briefly, then dealt with the measuring instruments of Ibn Majid.As for the second topic, it dealt with Ibn Majid's relationship with Portugal, and I tried in thisThe researcher clarified all the stories and events related to Vasco de Gama's trip to India, and thenI talked about the opinions of Arab historians in refuting this charge, then the last topicIn the manuscript that shows the identity of the guide who cooperated with the Portuguese, with the search appended to the translation.Arabic for the manuscript related to this topic.